Estrogen stabilizes hypoxia inducible factor 1 α through G protein coupled estrogen receptor 1 in eutopic endometrium of endometriosis - Zhang, Ling (Fertil Steril, 2016)
OBJECTIVE: To investigate whether G protein-coupled estrogen receptor (GPER, also known as GPR30 and GPER1) stabilizes Hypoxia inducible factor 1α (HIF-1α) in eutopic endometrium (EuEM) of endometriosis? DESIGN: Immunohistochemical analysis and experimental in vitro study. SETTING: University hospital PATIENT(S): Patients with or without endometriosis INTERVENTION(S): The EuEM and normal control endometrium (CoEM) were obtained by curettage. Primary cultured endometrial stromal cells (ESCs) were treated with 17β-estrogen (E(2)), G1 or G15. MAIN OUTCOME MEASURE(S): The EuEM and CoEM were collected for immunohistochemistry. Western blot, PCR, Elisa, and dual luciferase experiments were used to detect expression of GPER, HIF-1α, VEGF, and MMP9 in ESCs. E(2) and G1 were used as agonists of GPER while G15 as an antagonist. Migration of ESCs and endothelial tube formation of HUVECs cultured in medium collected from ESCs were measured. RESULTS: Protein levels of GPER and HIF-1α were higher in EuEM than in CoEM. HIF-1α protein levels but not HIF-1α mRNA levels increased concurrently with GPER after E(2) and G1 treatment. Furthermore, expression and activity of VEGF and MMP9 increased under E(2) and G1 stimulation. However these effects disappeared when GPER was blocked. CONCLUSION: GPER stabilizes HIF-1α thus promotes HIF-1α induced vascular endothelial growth factor (VEGF) and matrix metalloproteinase 9 (MMP9) in ESCs, which plays critical roles in endometriosis.